ASSIMILATING AND REPRODUCING CONCEPTS AFTER PHARMACOLOGY LECTURE - A QUESTIONNAIRE-BASED STUDY - SREEDHARAN, SYAM; PALAPPALLIL, DHANYA SASIDHARAN; VEEDU, LAILA KANDATH; KN, HARI SANKAR; MUTHANATTU DIVAKARAN, ATHIRA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Medical undergraduates learn pharmacology during the second phase of MBBS. Considering the expanding list of drugs and volatility associated with its learning, the objective of this study was to describe the factors that interfere with the assimilation and reproduction of the concepts in pharmacology. Methods: This was a descriptive study done in the Department of Pharmacology of a Government Medical College in Central Kerala for a period of 2 months. Five short answer questions were chosen to elicit responses from the participants in the form of a surprise test. A Google fill out form elicited the perception of the participants about learning during the pharmacology lecture. The data were sorted and entered into Statistical Package for the Social Sciences (SPSS) software version 16 (SPSS Inc, Chicago, USA). Descriptive data were expressed using frequencies and percentages. Results: Of the 148 students, 84 (56.75%) participated in the study. For the surprise test, the mean marks scored were 2.24±0.77 (maximum marks 5). Forty-seven (56%) participants claimed that they were attentive in pharmacology lectures only “sometimes.” The majority of the participants 82 (97.6%) “sometimes” found it difficult to imbibe the concepts in pharmacology. Seventy (83.3%) agreed that definitions are difficult to learn as such. Only 10 (11.9%) disagreed with the statement that a drug’s action cannot be interpreted as its use because sometimes actions can aggravate some diseases. Sixty-one (72.6%) participants had difficulty in understanding the word “rationale.” Five minutes break, continuity of topics, separate question-answer session at the end of class, summarization, a video demonstration of the mechanism of action, providing printed lecture notes, simple explanation, mnemonics to learn, clinical correlation, lectures during morning hours, and team-based quizzes were some suggestions to increase the assimilation of the subject. Conclusion: Participants had a mean score which was <50% of the total score. While the scores for definitions varied the question on uses of drugs fetched similar marks; however, the students had poor performance on the question related to rationale. Ignorance about the meaning of the word “rationale” shows the importance of regular feedback and the use of simple language in understanding the problems faced by the participants in learning the concepts in pharmacology.